Pemanfaatan ragi sebagai penyeimbang bahan baku berserat dalam formulasi pakan ikan nila (Oreochromis niloticus) - Telleng, Dewi; Lumenta, Cyska; Monijung2, Revol D (Universitas Sam Ratulangi, 2016)
This study was conducted to determine the effect of yeast as a counterweight of fibrous raw material in Tilapia feed formulations on growth and feed efficiency value. The research results found that the biggest absolute growth of Tilapia fry occurred in treatment A: 5% yeast (9,2 g), followed by C: 15% yeast (8,6 g), D: 20% yeast (7,14 g), and B: 10% yeast (5,03 g). The highest feed efficiency value occurred in treatment A (23,75%), followed by C (22,45%), D (18,69%) and B (13,96%). The parameter of water quality measured during experiment included temperature 26-28o C and pH 7. The range value of water quality in each treatment was considered to be proper for the living condition of fish fry. Keywords: yeast, Oreochromis niloticus, growth, feed efficiency